Inactivation of Bacterial Bioterrorism Agents in Water: A Summary of Seven USEPA and CDC Research Studies. Issue 4 (1st April 2013) - Spence, Shannon; Minamyer, Scott; Lee Menefee, Constance
Abstract : Past use of weaponized Bacillus anthracis spores has prompted increased interest in studying the inactivation of potential bacterial bioterrorism agents in drinking water. Conditions for chemically inactivating many regulated waterborne disease‐causing species are well known, but there are only limited data available on inactivating microorganisms that could potentially be used as biological weapons. Information on the likelihood of such agents surviving in drinking water containing disinfectants is needed to ensure that end users are sufficiently protected.